The influence of pregnancy classes on the use of maternal health services in Indonesia - Khadijah Azhar; Ika Dharmayanti; Dwi Hapsari Tjandrarini; Puti Sari Hidayangsih (BMC, 2020)
Abstract Background Indonesia has developed the pregnancy class program for mothers in an effort to reduce the high maternal mortality rate. This study aims to understand the influence of pregnancy classes on mothers' use of maternal and neonatal health services, which are known to improve pregnancy and delivery outcomes. Methods This study used data on members of households in communities in Indonesia, based on the 2016 National Health Indicators Survey (Sirkesnas), which covered 34 provinces and 264 districts/cities. The analysis focused on a sample of women ages 10-54 years who had ever been married and had given birth in the previous 3 years. The study analyzed three behaviors as outcome variables: whether a mother had adequate antenatal care, used a skilled birth attendant, and had a facility-based delivery. Logistic and multinomial logistic regression analysis was used to explore those relationships. Results 29% of mothers utilized adequate antenatal care (a minimum of five antenatal care components and at least four antenatal care visits), 77% of mothers used skilled birth attendants for delivering their baby, and 76% of mothers used a health facility to give birth. Only 7% of mothers participated in the complete pregnancy class program. Mothers who completed participation in the pregnancy class program had 2.2 times higher odds of receiving adequate antenatal care [OR = 2.19; 95% CI: 1.62 to 2.97; P < 0.001]. Those who completed participation in the class had 2.7 times higher odds of using skilled birth attendants for delivery [OR = 2.69; 95% CI: 1.52 to 4.76; P < 0.001] and 2.8 times higher odds of giving birth in a health facility compared to a non-health facility [OR = 2.77; 95% CI: 1.56 to 4.91; P < 0.001]. Conclusions Participation in pregnancy classes was positively associated with utilization of adequate antenatal care, skilled birth attendants, and delivery at health facility. Since participation in pregnancy classes in positively associated with maternal healthcare utilization, policy efforts should focus on improving implementation of the KIH program at the local level.